History and Feminization of Maulud Religious Celebration among Muslim Women of Dandume, Katsina State, Nigeria, 1995-2014 - Mubarak Tukur; Halima Bako (LAPAI JOURNAL OF NIGERIA HISTORY, 2021)
One important feature of Sufi brotherhood of Northern Nigeria, is the practice of Maulud (Muslim celebration of the birthday of the Prophet Muhammad). In the emirates of Northern Nigeria where Islam has fully entrenched for centuries, the practice of Maulud has been patriarchal, not until very recent, when one Sufi Muslim woman scholar, Sayyida Rahmatullahi single-handedly ventured into the organization and execution of this religious activity. This paper therefore, attempts to explore the role of this distinguished Tijjaniya female scholar who initiated this spiritual religious practice of Maulud celebration as a form of Da’awa in some villages, cities and towns of Dandume in Northern Nigeria. She is one of the prominent first female Tijjaniya Islamic scholar who started to organize a women based Maulud celebration. The Maulud – is a celebration of the birthday of the prophet. It is observed by members of the Tijjaniya brotherhood. The ceremony was attended by thousands of women from different parts of Northern Nigeria. The paper will also examine aspects of her scholarship and initiation into the Tijjaniyya Sufi order, and how the Maulud activity created a network of Islamic scholarship among female Sufi scholars and their students in the area. The paper adopts both primary and secondary sources of historical research methodology. Oral interviews were conducted with her students, associates and others. Also, related written works on the area are utilized. As such this paper will adopt the theory which is a “critic of Islamic Feminism” in Northern Nigeria. It is total departure from Islamic feminist struggle and activism, agitating for the re-interpretation of the religion or advocating for a space within the public domain in analyzing the feminine role and contribution of this woman scholar in the Patriarchal society of Northern Nigeria.